Obstacle Avoidance Algorithm for 7-DOF Redundant Anthropomorphic Arm. (28th January 2015) - Shen, Haoyu; Wu, Hongtao; Chen, Bai; Jiang, Yanjie; Yan, Cheng
Abstract : To deal with the problem of obstacle avoidance for redundant robots, an obstacle avoidance algorithm based on the internal motion of the 7-DOF redundant anthropomorphic arm is presented. The motion of that critical points move away from the closest points on the obstacles is defined as obstacle avoiding motion. Two transitioning variables were used to make a smooth, continuous transition between the primary and the secondary tasks. Using this approach, the robot can get the target configuration while avoiding the obstacles. Finally, the validity of the obstacle avoidance algorithm based on transitioning between tasks is manifested by simulation. The results show that, for the obstacle avoiding problem, the redundant robot not only can realize the obstacle avoidance, but also prevents the conflict between tasks by the proposed approach.